IntegrasiTauhid dan Akhlak dalam Pandangan Fakhruddîn Ar-Razi - Jarman Arroisi (TSAQAFAH, 2013)
This paper is based on deviation of mindset, attitudes, and human behavior that happened this nowadays. The deviation can be captured through the attitudes and behavior that is no longer based on human nature, but based on the lust. As a result, there is a moral degradation that led to the multi- dimensional crisis. Actually, the previous Islamic scholars, such as Fakhruddîn ar-Râzî had stressed the importance of establishing the mindset, attitude, and behavior on the basis of tawhid or human nature. In Islam, tawhid has a central position. It is the source of mindset, attitudes, and human behavior. Therefore, if tawhid is true, the behavior should be true, and also on the contrary. In Islam, between tawhid and mindsets, attitudes and behavior, have a close relationship, even they may not be separated. The attitudes of a believer, according to ar- Râzî, are being pious, keeping away from dirty deeds, do not hurt others, and do not do things that are prohibited. Meanwhile, the attitudes of musyrik are stubborn, do not believe and reject the truth. Likewise with the deeds. The kindness which is performed by people with correct tawhid should be different with the kindness done by others. The people who has correct tawhid do good thing simply because the worship of God, while those who has not correct tawhid do something based on humanitarian grounds. This matter, in the perspective of tawhid, can be categorized as riya’ and therefore, according to ar-Râzî, can be called by disobedience.